2019
DOI: 10.1016/s1470-2045(18)30905-7
|View full text |Cite
|
Sign up to set email alerts
|

Olaparib and α-specific PI3K inhibitor alpelisib for patients with epithelial ovarian cancer: a dose-escalation and dose-expansion phase 1b trial

Abstract: Gerburg M. Wulf and Ursula A. Matulonis contributed equally to this work CONTRIBUTORS PAK contributed to study concept, design, oversight, data collection and interpretation and writing of the manuscript. WTB contributed to the study design, data analysis and interpretation, writing and creation of figures. MB, LCC, JFL, MKB contributed to patient recruitment and study design and conception. CA and RLC and SNW contributed to the study design, data interpretation, critically reviewed manuscript drafts. ROC cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(142 citation statements)
references
References 35 publications
2
134
0
Order By: Relevance
“…PARP inhibitors further synergize with inhibitors of the PI3K pathway, as shown in BRCA-proficient TNBC, BRCA1 mutated breast cancer mouse models, PIK3CA mutated ovarian cancer cells, and PTEN mutated endometrial cancer cells Juvekar et al 2012;Wang et al 2016b;Philip et al 2017). A phase I clinical trial revealed synergistic effects between olaparib and the PI3K inhibitor alpelisib in epithelial ovarian cancer, which are most likely based on HR suppression through reduced RAD51 protein levels and RAD51 foci formation (Konstantinopoulos et al 2019). The combination of talazoparib and the mTOR inhibitor everolimus synergistically kills BRCA-proficient TNBC by inducing HR deficiency through repression of the histone methyltransferase SUV39H1 (Mo et al 2016).…”
Section: Inhibitors Of Transcription Regulators and Epigenetic Modifiersmentioning
confidence: 97%
“…PARP inhibitors further synergize with inhibitors of the PI3K pathway, as shown in BRCA-proficient TNBC, BRCA1 mutated breast cancer mouse models, PIK3CA mutated ovarian cancer cells, and PTEN mutated endometrial cancer cells Juvekar et al 2012;Wang et al 2016b;Philip et al 2017). A phase I clinical trial revealed synergistic effects between olaparib and the PI3K inhibitor alpelisib in epithelial ovarian cancer, which are most likely based on HR suppression through reduced RAD51 protein levels and RAD51 foci formation (Konstantinopoulos et al 2019). The combination of talazoparib and the mTOR inhibitor everolimus synergistically kills BRCA-proficient TNBC by inducing HR deficiency through repression of the histone methyltransferase SUV39H1 (Mo et al 2016).…”
Section: Inhibitors Of Transcription Regulators and Epigenetic Modifiersmentioning
confidence: 97%
“…between PARP inhibition and HR deficiency by simultaneous chemical inhibition of PARP and HR in cells genetically proficient for HR [22]. Such chemically induced synthetic lethal approaches open the possibility of treating many types of cancer that are either deficient or proficient for HR.…”
Section: Box 1 Dna Double-strand Break Repairmentioning
confidence: 99%
“…16 Alpelisib in combination with olaparib also induced a noteworthy preliminary clinical response in epithelial ovarian cancer. 17 In the future, treatment opportunities for PAMs may increase for the treatment of a variety of malignant tumours harbouring PAM pathway alterations. We suggest that intense infection control and prevention might be required in the treatment with PAMs, especially in the use of dual inhibitors.…”
Section: Discussionmentioning
confidence: 99%